Digital Referendum - Effective Modeling of Public Administration in Georgia - Khatuna Muradishvili; Ekaterina Zakaradze (European Scientific Journal, ESJ, 2023)
State management in its content is a complex and at the same time dynamic process. The second half of the 20th century can be considered the initial period of management transformation and establishment of governance structures. Governance based on democratic principles is based on a number of fundamental principles, the correct implementation of which is the most important prerequisite for the establishment of democratic institutions. One such important democratic process is the referendum. In Europe, the practice of referendum is most established in Switzerland, which is governed by a system of direct democracy. Accordingly, in order to solve problematic issues, citizens in Switzerland take part in both regional and national referendums, which are undoubtedly democratic in content and respond to the fundamental principles of modern public administration. In Georgia, where there is little experience in holding a referendum, the implementation of a digital referendum is the latest challenge, which will be an important step in the way of the country's European integration. The involvement of citizens in the solution of important issues for the state allows the so-called possibility of communication between society and government. It eliminates "black holes" and ensures the reduction of conflicts between them. Of course, all the positive results of the referendum depend on how fairly and objectively it will be conducted. Thus, one of the important challenges of the digitalization of the public administration of Georgia is the digital referendum, the implementation and development of which is an effective step on the way of the state development of Georgia and as a result ensures the acceleration of the country's institutional and European integration processes.